2014
DOI: 10.3892/ol.2014.2668
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the uterine cervix in pregnancy: A case report and review of the literature

Abstract: Abstract. The occurrence of cervical cancer during pregnancy is extremely rare, particularly small cell carcinoma. Small cell cervical carcinoma (SCCC) is a neuroendocrine tumor with a poor prognosis. This study presents the case of an 18-year-old female with stage IB2 SCCC complicated by pregnancy, who was treated with chemotherapy and radiotherapy. The patient was diagnosed shortly after giving birth, and is the youngest female case to be reported in the world. The patient was treated with cisplatin and etop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Although Syn and CgA were commonly used immnunohistochemical markers for diagnosis of SCC, different positive rates of each antibody were reported either in cervical SCC or in pulmonary SCC in different studies. [ 16 , 17 ] It was found that Syn had higher expression in the cervical SCC than in the pulmonary SCC in this research, which might be caused by the deviation of specimen selection.…”
Section: Discussionmentioning
confidence: 72%
“…Although Syn and CgA were commonly used immnunohistochemical markers for diagnosis of SCC, different positive rates of each antibody were reported either in cervical SCC or in pulmonary SCC in different studies. [ 16 , 17 ] It was found that Syn had higher expression in the cervical SCC than in the pulmonary SCC in this research, which might be caused by the deviation of specimen selection.…”
Section: Discussionmentioning
confidence: 72%
“…Wang et al and Balderston et al reported complete remission with a combination of chemotherapy and radiation therapy in lieu of radical surgery, with Balderston et al utilizing a regimen of cisplatin/etoposide alternated with vincristine/dactinomycin/ cyclophosphamide. 16,17 Given the paucity of data on small cell cervical carcinoma in pregnancy, no standard treatments have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year disease-specific survival in stage I-IIA, IIB-IVA, and IVB disease was 36.8%, 9.8%, and 0%, respectively [3]. Because of its rarity, no standardized treatment has been established for this carcinoma and therefore intensive chemotherapy and/or chemoradiotherapy similar to that used for lung small cell carcinoma have been applied with only modest success [3][4][5][6]. The present case was refractory to platinum-based chemotherapy, and the patient strongly desired new treatments in addition to radiation therapy of the pelvic lymph node metastases, and we administered both AFTV and anti-PD-1 antibody, although these drugs are still unauthorized for cervical cancer in Japan.…”
Section: Discussionmentioning
confidence: 99%